Factors associated with psychological wellbeing, is education one of them? - Gholamreza Oskrochi; Youssof Oskrochi; Rogheyeh Eskrootchi (PLoS ONE, 2026)
Many factors, such as health, marital status, social relationships, and job status, influence psychological wellbeing. Previous research has suggested that educational attainment is also a key contributor to a happier life. Utilising data from the Understanding Society survey (2010 -2018), we conducted a comprehensive analysis of the direct and indirect effects of education on psychological wellbeing of 68,283 individuals in the UK. After controlling for relevant variables, we identified a direct association between educational attainment and psychological wellbeing. This aligns with earlier studies examining the link between education and happiness. While some of these studies report significant positive relationships, our results underscore the complexity of factors influencing psychological wellbeing, extending beyond education alone.